Peningkatan keterampilan membaca pemahaman cerita anak melalui penggunaan model pembelajaran visualization, auditory, and kinestethic peserta didik kelas v sekolah dasar - Nora Dwijayanti; Muhammad Ismail Sriyanto; Karsono Karsono (Didaktika Dwija Indria, 2019)
Abstract. The purpose of this research is to improve the reading comprehention skills of children’s story through the use of learning models Visualization, Auditory, and Kinestethic (VAK). This is an action classroom research that carried out for two cycles. Every cycle consist of four steps there are planning, implementation, observation, and reflection. Technique that used for collect data are observation, interview, test, and documentation. The data validity test technique uses content validity and triangulation. The data analysis technique uses interactive model learning. The result of this research showed that the initial pre-action test score were 47.33 with classical completeness of 10.34%, increased in the first cycle by 69,71 with classical completeness of 51.73%, then in second cycle it increased significantly to 80.36 with classical completeness of 86.21%. Referring to the results of this reserch it can be conclude that the use of VAK learning models can improve the reading comprehention skills of children’s story in fifth grades students of SDN Sayangan No.244 Surakarta academic year 2018/2019.   Keywords: Visualization, Auditory, and Kinestethic (VAK), comprehention reading sklills children’s story, Elementary School